208k views
1 vote
Make v the subject of the formula in H=m(v²-u²)/2gx​

User Lanorkin
by
5.5k points

1 Answer

13 votes

Answer:


v=\sqrt{(H* 2gx)/(m)+u^2}

Explanation:

The given formula is :


H=(m(v^2-u^2))/(2gx)

We need to find the formula for v.

Cross multiplying the given formula.


H* 2gx=m(v^2-u^2)

Dividing both sides by m. So,


(H* 2gx)/(m)=(m(v^2-u^2))/(m)\\\\(v^2-u^2)=(H* 2gx)/(m)

Adding both sides by u².


(v^2-u^2)+u^2=(H* 2gx)/(m)+u^2\\\\v^2=(H* 2gx)/(m)+u^2\\\\\text{So},\\\\v=\sqrt{(H* 2gx)/(m)+u^2}

Hence, this is the required formula.

User DDRamone
by
5.6k points